Evaluation of visual function in Royal College of Surgeon rats using a depth perception visual cliff test. (31st January 2019) - Tzameret, Adi; Sher, Ifat; Edelstain, Victoria; Belkin, Michael; Kalter-Leibovici, Ofra; Solomon, Arieh S.; Rotenstreich, Ygal
Abstract: Preserving of vision is the main goal in vision research. The presented research evaluates the preservation of visual function in Royal College of Surgeon (RCS) rats using a depth perception test. Rats were placed on a stage with one side containing an illusory steep drop ("cliff") and another side with a minimal drop ("table"). Latency of stage dismounting and the percentage of rats that set their first foot on the "cliff" side were determined. Nondystrophic Long–Evans (LE) rats were tested as control. Electroretinogram and histology analysis were used to determine retinal function and structure. Four-week-old RCS rats presented a significantly shorter mean latency to dismount the stage compared with 6-week-old rats (mean ± standard error, 13.7 ± 1.68 vs. 20.85 ± 6.5 s, P = 0.018). Longer latencies were recorded as rats aged, reaching 45.72 s in 15-week-old rats ( P < 0.00001 compared with 4-week-old rats). All rats at the age of 4 weeks placed their first foot on the table side. By contrast, at the age of 8 weeks, 28.6% rats dismounted on the cliff side and at the age of 10 and 15 weeks, rats randomly dismounted the stage to either table or cliff side. LE rats dismounted the stage faster than 4-week-old RCS rats, but the difference was not statistically significant (7 ± 1.58 s, P = 0.057) and all LE rats dismounted on the table side. The latency to dismount the stage in RCS rats correlated with maximal electroretinogram b-wave under dark and light adaptation (Spearman's rho test = −0.603 and −0.534, respectively, all P < 0.0001), outer nuclear layer thickness (Spearman's rho test = −0.764, P = 0.002), and number of S- and M-cones (Spearman's rho test = −0.763 [ P = 0.002], and −0.733 [ P = 0.004], respectively). The cliff avoidance test is an objective, quick, and readily available method for the determination of RCS rats' visual function.